Three karchacks : Lha ldan sprul paʼi gtsug lag khang gi dkar chag shel dkar me long (1645) - Ṅag-dbaṅ-blo-bzaṅ-rgya-mtsho, Dalai Lama V, 1617-1682; Phur-bu-lcog Ṅag-dbaṅ-byams-pa, 1682-1762; Demo, Ngawang Gelek, 1939- (Gedan sungrab minyam gyunphel series, 1970)
Surveys of objects of veneration of several important religious establishments of Tibet; includes a comprehensive list of xylograph blocks to be found in the printing establishments of central Tibet (DS-Z)